Long-Term Effects of Degradation on Photovoltaic System Return on Investment (2023)
The adoption of photovoltaic (PV) systems has increased significantly in recent years, driven by the demand for off-grid and on-grid residential and commercial applications. However, the high initial investment required for PV installations has limited their widespread adoption. Governments and marketing enterprises have implemented different strategies to promote PV systems to overcome this barrier, focusing on the return on investment (ROI) concept. However, the conventional approach uses limited economic factors to calculate the ROI. It fails to consider the impact of external factors, such as system degradation, which can vary between systems. To address this issue, we propose a new methodology to estimate the ROI of a photovoltaic system with greater accuracy. Our approach incorporates system-predicted degradation, calculated using historical meteorological data and prediction techniques. We applied this methodology to a photovoltaic system installed at the Universidad Tecnologica de Bolivar (UTB) in Cartagena and evaluated it against five different approaches. The results show that our proposed method offers a more accurate and reliable estimation of the ROI of a photovoltaic system, considering a broader range of factors. Overall, our work contributes to advancing the understanding of photovoltaic system ROI calculation and promotes using sustainable energy sources. By providing a more precise estimation of the ROI of a photovoltaic system, our methodology can help potential investors make more informed decisions and promote the adoption of clean energy sources.